Distribution and modes of occurrence of heavy metals in opposed multi-burner coal-water-slurry gasification plants. (1st November 2021) - Jiang, Peng; Xie, Cheng-rui; Luo, Chun-lin; Meng, Wei; Yang, Gang; Yu, Guang-suo; Gong, Yan; Xu, Mengxia; Wu, Tao
Highlights: Migration of heavy metals during OMB coal gasification was studied. Fine slags are of higher concentration of most of the nine heavy metals (HMs). Residual fraction was the main form of HMs in both fine and coarse slags. Mobile fraction of HMs in fine slags was greater than that of coarse slags. Except Cu, the other HMs in slags exceeded the standard for direct landfill. Abstract: To understand the migration and modes of occurrence of heavy metals in the opposed multi-burner (OMB) coal-water-slurry (CWS) gasification process, samples of coal, coarse and fine slags were obtained from two plants with different capacities. Concentrations of nine hazardous heavy metals (HMs) in these samples, i.e., Ba, Co, Cr, Cu, Mn, Ni, Pb, V, and Zn, were determined to show their migration and enrichment behaviours. A four-step sequential extraction method was implemented to reveal the modes of occurrence of these HMs. Results demonstrated that fine slags were mainly fragmentized spheres and were covered by fine floccules, whilst coarse slags were vitreous, angular and less porous than fine slags. Majority of the heavy metals were more concentrated in fine slags. Chromium was enriched in coarse slags, while Pb and Zn were accumulated in fine slags as indicated by the relative enrichment index. The sequential extraction demonstrated that for the coals, Cr, Cu, Ni, V and Zn were primarily associated with residual fractions (48.8–82.6 wt%), while Co, Mn and Pb were dominant in oxidizable (78.1 wt%), acid soluble (60.0 wt%) and reducible fractions (99.2 wt%), respectively. In fine slags, except for Zn, the other HMs were mainly distributed in residual fraction with 42.3 to 94.8 wt% in fine and coarse slags, respectively. Mobile fraction of HMs was the highest in coals (19.4–93.6 wt%), followed by fine slags (11.6–73.1 wt%) and coarse slags (5.1–41.0 wt%). Based on the leaching ability, except Cu, the HMs content in all slags were above the standard for direct landfill disposal.